Answer:
a)2.46 %
b)For 1 :101.52 %
For 2 : 99.08 %
c)100..4 %
Explanation:
Given that
g₁ = 9.96 m/s²
g₂ = 9.72 m/s²
The actual value of g = 9.8 m/s²
a)
The difference Δ g = 9.96 -9.72 =0.24 m/s²
b)
For first one :
For second :
c)
The mean g(mean )
a)2.46 %
b)For 1 :101.52 %
For 2 : 99.08 %
c)100..4 %
The percent difference between the two measurements is 2.44%. The percent error for the first measurement is 1.63%, and for the second measurement is 0.82%. The percent error of their mean is 0.41%.
In physics, the percent difference is calculated by subtracting the two values, taking the absolute value, dividing by the average of the two values, and then multiplying by 100. Therefore, the percent difference between the two measurements 9.96m/s² and 9.72m/s² is:
|(9.96-9.72)|/((9.96+9.72)/2)*100 = 2.44%
The percent error involves taking the absolute difference between the experimental value and the accepted value, divided by the accepted value, then multiplied by 100. So, the percent error for the two measurements with accepted value of 9.80m/s² are:
For 9.96m/s²: |(9.96-9.80)|/9.80*100 = 1.63%
For 9.72m/s²: |(9.72-9.8)|/9.8*100 = 0.82%
The percent error of the mean involves doing the above but using the mean of the experimental measurements:
|(Mean of measurements - Accepted value)|/Accepted value * 100 |(9.96+9.72)/2-9.8|/9.8*100 = 0.41%
#SPJ3
Answer:
The angular speed of the system at the instant the beads reach the ends of the rod is 14.87 rad/s
Explanation:
Moment of inertia is given as;
I = ¹/₁₂×ML² + 2mr²
where;
I is the moment of inertia
M is the mass of the rod = 0.19 kg
L is the length of the rod = 0.43 m
m is the mass of the bead = 0.038 kg
r is the distance of one bead
Initial moment of inertial is given as;
Final moment of inertia is also given as
Angular momentum is the product of angular speed and moment of inertia;
= Iω
From the principle of conservation of angular momentum;
Given;
ωi = 12 rad/s
r₁ = 10.0 cm = 0.1 m
r₂ = 10.0cm/4 = 2.5 cm = 0.025 m
Substitute these values in the above equation, we will have;
Therefore, the angular speed of the system at the instant the beads reach the ends of the rod is 14.87 rad/s
Explanation:
It is given that,
Mass of the passenger, m = 75 kg
Acceleration of the rocket,
(a) The horizontal component of the force the seat exerts against his body is given by using Newton's second law of motion as :
F = m a
F = 3675 N
Ratio,
So, the ratio between the horizontal force and the weight is 5 : 1.
(b) The magnitude of total force the seat exerts against his body is F' i.e.
F' = 3747.7 N
The direction of force is calculated as :
Hence, this is the required solution.
The horizontal component of the force the seat exerts against the passenger's body is 3675 N. The ratio of this force to the passenger's weight is 5. The total force the seat exerts has a magnitude of 3793 N.
(a) To calculate the horizontal component of the force the seat exerts against the passenger's body, we can use Newton's second law, which states that force is equal to mass times acceleration. In this case, the mass of the passenger is 75.0 kg and the acceleration of the rocket sled is 49.0 m/s2. So the force exerted by the seat is:
Force = mass * acceleration
Force = 75.0 kg * 49.0 m/s2
Force = 3675 N
Now let's compare this force to the passenger's weight. The weight of an object is given by the formula:
Weight = mass * gravitational acceleration
Weight = 75.0 kg * 9.8 m/s2
Weight = 735 N
To find the ratio, we divide the force exerted by the seat by the weight of the passenger:
Ratio = Force / Weight
Ratio = 3675 N / 735 N
Ratio = 5
(b) The total force the seat exerts against the passenger's body has both a horizontal and vertical component. The direction of the total force is the same as the direction of the acceleration of the rocket sled. The magnitude of the total force can be found using the Pythagorean theorem:
Total Force = √(horizontal component2 + vertical component2)
Total Force = √(36752 + 7352)
Total Force = 3793 N
#SPJ11
a.rubber
b.iron
c.copper
d.aluminum
the answer is false. Hope this helps
Answer:
The slower runner is 1.71 km from the finish line when the fastest runner finishes the race.
Explanation:
Given;
the speed of the slower runner, u₁ = 11.8 km/hr
the speed of the fastest runner, u₂ = 15 km/hr
distance, d = 8 km
The time when the fastest runner finishes the race is given by;
The distance covered by the slower runner at this time is given by;
d₁ = u₁ x 0.533 hr
d₁ = 11.8 km/hr x 0.533 hr
d₁ = 6.29 km
Additional distance (x) the slower runner need to finish is given by;
6.29 km + x = 8km
x = 8 k m - 6.29 km
x = 1.71 km
Therefore, the slower runner is 1.71 km from the finish line when the fastest runner finishes the race.